Smart Tourism Perspectives on TikTok-Driven Cultural Visits: Evidence from Pacu Jalur Festival - Muhamad Zhabiyan Dwi Putra; Ryan Danung Adean; Ellysia Augris; Fahmi Muhamad Rizky; Audy Azzahra Vania; Fajar Anugrah Dwi Setiawan (MDP Student Conference, 2026)
Pacu Jalur cultural tourism attracts wide public interest, particularly for its historical value and rich traditional heritage in Riau, Indonesia. In recent years, its appeal has increased through the circulation of visual content on social media platforms, especially TikTok. However, scholarly studies examining the influence of digital content on visit intention to cultural tourism destinations remain limited. This study addresses that gap by analyzing the relationship between perceived entertainment, destination image, and visit intention toward the Pacu Jalur festival. Utilizing a quantitative approach and Structural Equation Modeling (SEM-PLS), data were collected from 167 respondents who had seen the TikTok trend related to Pacu Jalur. The results indicate that perceived entertainment significantly affects both destination image and visit intention. Furthermore, destination image plays a mediating role in the relationship between entertainment and visit intention. These findings demonstrate that user-generated, visually engaging, and culturally authentic content on social media can enhance destination perceptions and increase visit motivation, particularly among younger audiences. The study offers theoretical contributions in digital tourism and practical implications for cultural promotion strategies through social media in preserving intangible heritage.